Avifauna Composition at Tenghilan Community Forest: A Preliminary Assessment - Logananthini Solayappan; Lim, Wing-Shen; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2021)
The avian community plays an important role in maintaining the ecosystem at Tenghilan Community Forest in equilibrium, and yet the existing condition of the local avifaun a community has yet been investigated by the researchers at this moment. Henceforth, a preliminary mist-net survey was conducted for 6 days, to determine the species composition of avifauna presented at three different forest trails in this state land for st. A total of 48 individuals and 22 species of avian belonged to 13 different families were recorded in this research. The detected avian individuals were comprised mainly of the insectivorous (n=29 or 60.4 %) species and followed by the omnivorous (n=7 or 14.6 %) species, and finally both the carnivorous species and frugivorous species (n=6 or 12.5 % respectively; Χ2 63=144.0, p<0.001). There were no significant differences in the diversity richness and distribution evenness of avian species between the three selected forest trails (p>0.05), therefore indicating that the local avifauna species were rich in diversity (H’ > 1.5) and evenly distributed (1 - D>0.5) across the Tenghilan Community Forest. However, further study should be conducted at thi s state land forest by covering a wider sampling area, also a longer sampling period in future.